The Effect of Ownership Structure, Audit Committee Size, Company Size, Audit Quality, Chief Executive Officer (CEO) Gender on a Company's Timeliness (Empirical Study on Energy Sector Companies Listed on the IDX for the 2019-2022 Period) - Rahayu, Sri; Ridwan, Muhammad; Rizka, Sinthia (Faculty of Economics and Business Universitas Jambi, 2025)
This study aims to provide empirical evidence on the effect of ownership structure, audit committee size, company size, audit quality, and Chief Executive Officer (CEO) gender on the timeliness of financial reporting in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The issue of timeliness is critical in enhancing the relevance and reliability of financial information for stakeholders. This quantitative research uses secondary data obtained from company annual reports, with a sample of 196 firm-year observations selected through purposive sampling. The data were analyzed using descriptive statistics and logistic regression with the aid of SPSS version 29. The results reveal that both partially and simultaneously, the variables tested— ownership structure, audit committee size, company size, audit quality, and CEO gender—do not significantly affect the timeliness of financial reporting. These findings suggest that other factors outside the observed variables may play a more dominant role in determining financial reporting timeliness, indicating the need for broader research in the future